Clinico-epidemiological profile and predictors of in-hospital outcome of acute poisoning cases in children of Northern India - K, Muhammed Yasir; Kumar, Ajay; Kapoor, Kanika; Kumath, Manish; Aggarwal, Kailash Chander (Indian Journal of Child Health, 2019)
Background: Childhood poisoning is a common but preventable problem worldwide with incidence varying from 0.3% to 7.6%. Demography, socioeconomic status, education, local belief and customs, occupation, religious, and cultural influences determine the cause of poisoning. Aim: This study was conducted to understand the recent changes increasing urbanization and rapid socioeconomic development in India during the past decade and to find out the change in pediatric due to poisoning profile. Materials and Methods: This study was conducted in a pediatric ward of a tertiary care hospital in North India during the period of January 2016–December 2016. A total of 174 children admitted with acute poisoning in the hospital during the study tenure were enrolled for the study. Clinical and demographic data were recorded in a predesigned proforma and results were compared with the previous studies from the region. Results: Mean age at presentation was 3.7 years, wherein males outnumbered females. Accidental mode (97%) was the most common mode of poisoning while ingestion (99%) was the most common route of exposure. The common agents incriminated in decreasing order of frequency were corrosives (24.71%), pyrethroids (12.64%), and kerosene (9.77%). Majority of patients belongs to lower middle class (57%) and urban areas (61%). Most children present with mild symptoms, of them vomiting was the most common (65%) and 12.6% developed complications. Mean duration of hospital stay was 2.5±1.91 days with a mortality of 2.16%. Conclusion: There is changing pattern in acute poisoning in children with decline in incidence of kerosene and pesticide poisoning while increase in corrosives and parathyroid poisoning. Low Glasgow Coma Scale and time lapse between poisoning and presentation to the hospital can be a predictor of high mortality.